Adaptation to climate change in Asia - Vachani, Susshil; Usmani, Jawed (Cheltenham, UK Edward Elgar, 2014)
The frequency and scale of damage inflicted by climate-related disasters, including floods, drought, heat waves and hurricanes, has been increasing at an alarming rate. This volume provides a timely and thoughtful discussion of strategies for adaptation to climate change, which can complement mitigation strategies being developed by other experts throughout the world. The book focuses on eight geographically diverse territories in Asia, which are among the areas that will experience the most severe impacts of climate change and are the most vulnerable in terms of capacity to cope with the damage. The authors discuss adaptation strategies to safeguard food and water supplies, address urban problems, support migrant workers, protect coastal cities and preserve biodiversity. They also offer a critical analysis of plans that have proven successful to explore what additional steps can be taken to address the gaps. The collection of observations and recommendations in this book will prove invaluable to policy makers in countries that are facing similar threats and looking to build their adaptive capacity to cope with climate change. It will also appeal to academics interested in environmental ecology, sustainable development, global climate change and Asian studies.--Source other than Library of Congress.
Adaptation to climate change in Asia / Sushil Vachani and Jawed Usmani -- Vulnerable and lagging behind : the case of Hong Kong / Jolene Lin -- The evolution of environmental policies in South Korea in response to climate change / Ki-Ho Kim, Hye-Jin Jung and Chankook Kim -- Climate-proofing a concrete island : improving state and societal climate adaptation capacities in Singapore / Sofiah Jamil -- Assessing climate change impacts and adaptation strategies in China / Joanna I. Lewis -- Adaptation to climate change in Bangladesh : migration, the missing link / Tasneem Siddiqui and Motasim Billah -- Adaptation strategy to address climate change impacts in the mountains : the case of Nepal / Bhaskar Singh Karky -- Climate change adaptation in agriculture in Cambodia / Nyda Chhinh -- Adapting Indian agriculture to climate change / Sushil Vachani and Jawed Usmani.
Includes bibliographical references and index.
Keywords: Climatic changes -- Asia